Pengaruh Konten Tiktok Pandawara Group terhadap Sikap Peduli Lingkungan Gen Z - Rajudin, Abdullah Aziz; Hadi, Sigit Pramono (Al-DYAS, 2024)
Currently, it is undeniable that almost every hour or even minute, social media is always enjoyed by all groups, especially generation Z, social media is an interaction between one person and another creating, sharing, exchanging and modifying ideas or ideas in the form of virtual communication or internet networks in real time. The social media platform that is currently often in demand or popular in Indonesia is Tiktok. With Tiktok, a person or group can be famous or become viral because of the content they make, one of the TikTok accounts that is currently viral is the Pandawara Group. The Pandawara Group itself is a group of young people from Bandung who create content on Tiktok with clean-up actions in various places. This study aims to determine the influence of Tiktok Pandawara Group content on the environmental care attitude of Generation Z. This study uses a quantitative approach and positivism paradigm. The sampling method in research uses non-probability sampling techniques and purposive sampling methods. The results of this study indicate that Pandawara Group's TikTok content has a moderate positive influence on environmental care attitudes, namely 57.4%, while the remaining 42.6% is influenced by other variables not examined in this study.